História, catequeses e gênero: uma abordagem dos sentidos de família, maternidade e mulher em discursos da Igreja Católica (Uberlândia, 1978-2013) - Maciel, Adriana Simões Monteiro (2014)
This research aims to analyze the representations of family, marriage, motherhood and women in Catholic Church s discourse, based on the apostolic and encyclicals letters, Catholic Church s Catechism, catechesis on human love, produced in the pontificate of João Paulo II. Through other written documentary sources and inspired by Vatican II, including the informative O Vagalume and Diretrizes para a Catequese da Diocese de Uberlândia, analyzed sources observe the reality of Uberlândia city. With the aid of theoretical and methodological references that address the social imaginary, social representations and gender, we analyze the practices of catechesis, considering the relationship between the texts of doctrine and religious practices of Catholic women entered this religious field. The gender category is used to realize how social representations are constructed and engineered into the religious sphere, but also to observe the deviations of some Catholic women to the standard dictated by the Church. The purpose of this paper is to discuss the fact that women who classify themselves as Catholic and practitioners present tensions in certain situations, different views regarding the doctrine and guidelines for Catholic practice. Feminist Theology in conjunction with the gender category is presented as a movement within and outside the Church, we noted the adverse attitudes and religious practices of Catholic norms. An attempt is thus highlight the historical, Women practices, particularities within the Catholic character, demonstrating multiplicity of powers, although exercised discreetly, is present within the Church.